1998
DOI: 10.1111/j.1532-5415.1998.tb02475.x
|View full text |Cite
|
Sign up to set email alerts
|

ADVANCING GERIATRIC NURSING PRACTICE: Geriatric Nurse Practitioners in Long‐Term Care: Demonstration of Effectiveness in Managed Care

Abstract: The use of GNPs in collaboration with physicians reduced ED and acute care utilization costs as well as overall costs for a cohort of HMO enrollees in long-term care. This encouraged the HMO to support the concept that all long-term care HMO residents should be covered by GNP/MD teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 12 publications
1
65
1
Order By: Relevance
“…49,50 With the institution of diagnosis-related group payment systems in acute care hospitals, there was substantial motivation to reduce hospital bed days. Since then, hospitals have discharged patients "quicker and sicker" into nursing homes.…”
Section: The Impact Of Advanced Practice Nursing In Primary Carementioning
confidence: 99%
“…49,50 With the institution of diagnosis-related group payment systems in acute care hospitals, there was substantial motivation to reduce hospital bed days. Since then, hospitals have discharged patients "quicker and sicker" into nursing homes.…”
Section: The Impact Of Advanced Practice Nursing In Primary Carementioning
confidence: 99%
“…Much of the empiric evidence regarding the link between APN nursing home practice and positive resident outcomes relies on multiple reports of a single study of the EverCare demonstration project in five geographic locations, using administrative data in large part (Kane et al, 2001;Kane et al, 2002;Kane et al, 2004). Some studies were limited by the use of retrospective chart review (Burl, Bonner, Rao, & Khan, 1998) or by a survey that failed to report reliability or validity of the survey instrument (Abdallah, 2005). As well, the literature includes description of practice models implemented by APNs in one longterm care setting (Kennedy et al, 2000;Smith et al, 1995) or used relatively small sample sizes in a few facilities (Evans et al, 1997;Ryden et al, 2000).…”
Section: Outcomes Of Apn Indirect Carementioning
confidence: 98%
“…Only a few studies were identified that specifically linked the outcomes of APN practice with nursing home residents on the costs of that care. For example, a cost-effectiveness analysis of a geriatric nurse practitioner (gNP) and physician (MD) collaboration versus an MD-alone practice included transfer to emergency departments and acute and subacute care days as outcome variables (Burl et al, 1998). APN and physician teams providing care to HMO enrollees in 45 long-term care facilities were associated with lowering the cost of care as compared with physician care alone.…”
Section: Cost-effectiveness Research With Apnsmentioning
confidence: 99%
“…Studies also demonstrated that collaboration with midlevel practitioners including nurse practitioners (NPs) and physician assistants (PAs) in the post acute care period enhanced overall patients care, reduced emergency department use and hospitalization [49][50][51].…”
Section: Multidisciplinary Approachmentioning
confidence: 99%
“…Increased patient-physician communication is associated with improved outcomes [47]. Medico-legal case reports have associated poor interphysician communication with serious adverse outcomes [48].Studies also demonstrated that collaboration with midlevel practitioners including nurse practitioners (NPs) and physician assistants (PAs) in the post acute care period enhanced overall patients care, reduced emergency department use and hospitalization [49][50][51].Utilization of pharmacy consultants, monitoring for drug interactions, pharmacotherapy optimization and medication reconciliation during the various transfer process of the residents may also result in improvement in health care outcomes. Discussion and review of treatment goals and post discharge plan between the patient and family using an interdisciplinary team approach is crucial for success.…”
mentioning
confidence: 99%